Certain investigations on performance analysis of different converter designs for smart micro-grid systems - Krishnamoorthy, N.; Hanumanthakari, Sudheer; Sivasubramanian, Gobimohan; Prabha, A.; Hemachandu, P.; Veeramanikandan, P.; Medikondu, Nageswara Rao; Gopinathan, R.; Anbarasu, L. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper proposes a grid-connected hybrid renewable power system. A LUO converter driven by ABC-PI controller is used to produce stable DC-link voltage. To enhance the voltage, a LUO converter is used, and the boosted voltage is regulated by an ABC-PI controller. Using the suggested optimization approach, the power fluctuation is kept at a low value. The execution of the proposed optimization is efficient, as it is simple and robust. It has a limited number of control parameters as compared to other approaches. The suggested method is described in complete detail, together with its converter and control mechanisms. The modeling and experimental results are validated to ensure that the system is feasible. The HRES is analyzed through simulation in MATLAB with converters like boost, SEPIC, and LUO. The results reveal that the LUO converter performs better with a minimum settling time of 0.175 seconds with a source current THD of 1.29%. From the modeling and the simulation results, it has been revealed that the proposed technology provides more reliable and steady power.